Study of zinc hydroxy acetate as catalyst in the esterification reaction of fatty acids - Reinoso, Deborath Mariana (2012)
In this work, the esterification of oleic acid (OA) with methanol (MOH) using layered heterogeneous catalysts under various reaction conditions to produce biodiesel was studied. The zinc hydroxy nitrate salt Zn5(OH)8(NO3)2 · 2H2O (abbreviated Zn-N) and zinc hydroxy acetate Zn5(OH)8(CH3COO)2 · 4H2O (abbreviated Zn-A), which have a layered structure, were synthesized (chemical precipitation) and characterized. Tests for the selection of reaction conditions that maximize the yield to methyl esters were performed. The variables considered were temperature, OA:MOH molar ratio and catalyst loading, selecting the study intervals within the range of feasible operating conditions for the catalysts. The layered solid Zn-A was seen to be more active than Zn-N for the esterification of OA. When working at 140°C, 1:30 OA:MOH molar ratio and catalyst loading of 3% w/w, conversions of 87.0 and 73.4% were obtained for Zn-A and Zn-N, respectively.